Ellagic acid impedes carbontetrachloride-induced liver damage in rats through suppression of NF-kB, Bcl-2 and regulating Nrf-2 and caspase pathway - Aslan, Abdullah; Gok, Ozlem; Erman, Orhan; Kuloglu, Tuncay (Elsevier France-Editions Scientifiques Medicales Elsevier, 2018)
The use of natural antioxidants instead of conventional treatments is considered effective and safe alternative therapy for hepatotoxicity. Ellagic acid (EA) is a strong antioxidant matter having protecting effect particularly on the liver. Hepatotoxic compounds can cause very heavy damage. Among these chemical hepatotoxins, CCl4 are responsible for the trichloromethyl radical resulting from biotransformation of the liver. The aim of this study was to examine whether EA plays a protective role against to liver damage induced with carbon tetrachloride (CCl4) in rats. In this study, 36 male wistar albino (n = 36, 8 weeks old) rats were used. The rats were distributed into 4 groups, and 9 rats involved in each group. The groups were: (i) Control Group: Fed with standard diet; (ii) EA Group: Fed with standard diet + EA; (iii) CCl4 Group: Fed with standard diet + CCl4; (iv) CCl4 + EA Group: Fed with standard diet + CCl4 + EA. After 8 weeks, the rats were decapitated and the liver tissue were examined. As a result; EA application created a significant difference (p < 0.05) on caspase-3, bcl-2, NF-kB and Nrf-2 expression in the CCl4 + EA group in comparison to CCl4 group. Caspase-3 and Nrf-2 expression levels were increased in the CCl4 + EA group in comparison to CCl4 group, but bcl-2 and NF-kB expression levels were decreased. In TUNEL assay examinations, apoptotic index ratio was decreased in the CCl4 + EA group in comparison to CCl4 group. These results show that EA reduce liver damage ratio M wistar albino rats and also these results suggest that ellagic acid may be a potentially protective drug against to liver damage in future.
Keywords: Ellagic acid; Liver; Apoptosis; Caspase-3; Bcl-2; Nrf-2; NF-kB